Back to meetings: The 83rd Italian Congress on Occupational Health was held in Parma from 15th to 17th September 2021 - Spatari, Giovanna (La Medicina del Lavoro, 2021)
Traditional welcome greetings never had such an appropriate meaning as on this occasion. We have lived through a terrible period dominated by the COVID-19 pandemic and, for the first time in the long history of our Society, after dozens of annual editions, in 2020 our national Congress was cancelled. In addition to the obvious aspects of professional updating, our annual appointment plays an essential aggregative and social role in a broad sense. Furthermore, during the National Congress, the public presentation of documents and subsequent debate of our programmatic guidelines partly guides the Presidency and the Board in activities for the following year.[...]